66th Open Seminar on Acoustics Boszkowo, Poland, September 18 – 20, 2019 - OSA 2019, Chronicle (Archives of Acoustics, 2019)
The paper contains the abstracts of papers presented during 66th Open Seminar on Acoustics, Boszkowo, Poland, September 18 – 20, 2019